Tingkat kelangsungan hidup juvenil lobster air tawar ‘red claw’ (Cherax quadricarinatus) dengan pemberian pakan alami berbeda - Paputungan, Fikri; Mingkid, Winda M.; Sambali, Hariyani (Universitas Sam Ratulangi, 2021)
This study aimed to analyze the survival rate of freshwater crayfish Cherax quadricarinatus, using different natural feeds, namely Alona sp, Daphnia sp. and Artemia sp. Observing the growth of juvenile crayfish C. quadricarinatus. The study was conducted for two months (April - May 2019), at the Aquaculture Technology Laboratory. In this study, there were three treatments, namely different types of natural food. The treatments given were: Treat A Alona sp .; Treatment B Daphnia sp; and Treatment C Artemia sp. Feeding 25 individuals during the maintenance period is carried out twice a day, namely in the morning at 08.00 - 09.00 and 17.00 - 18.00 WIB. This study used a completely randomized design showing that the average value of SR (survival) in each treatment such as treatment A (Alona sp) was 60%, then treatment B (Daphnia sp) was 66.67% and finally treatment C ( Artemia sp) of 66.67%. Observation results for 21 days of mainten ance found an increase in length between 2 - 4 mm. The analysis of variance (ANOVA) showed that the differences in the types of natural food did not have a significant effect (P> 0.05) on the survival and growth of juvenile crayfish kept for 21 days